Analisis Struktur Ekonomi di Sumatera - Septriani Septriani (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2022)
Economic growth is often used as a benchmark for the success of economic development. To achieve successful development makes the government strive to create a high rate of economic growth. One of the strategies used by the government to create high economic growth is to spur sectors of the economy that can provide great added value in a short time. Economic growth that occurs continuously can cause changes in the economic structure of the region. Structural transformation means a process of changing the structure of the economy from the agricultural sector to the industrial or service sector, where each sector will undergo a different transformation process. The existence of the covid-19 pandemic not only has an impact on the health sector but also especially in the economic field. Sectoral economic growth contracted negatively where in 2019 Indonesia's sectoral economic growth of 5.02 percent decreased to -2.07 percent. The purpose of this study is to analyze changes in economic structure in Sumatra. The data to be collected includes PDRB data on a constant price basis in 2010. This research will use quantitative descriptive analysis techniques. The results of the study found that during 2010 to 2019, there was a change in economic structure on the island of Sumatra. The contribution of the agricultural sector fell while the tertiary sector increased. While the secondary sector increased during the period, but the increase was not so large.